Macrophages are important mediators of either tumor- or inflammation-induced lymphangiogenesis - Ji, Rui-Cheng (Cellular and molecular life sciences : CMLS, 2012)
The lymphatic system provides important functions for tissue fluid homeostasis and immune response. Lymphangiogenesis, the formation of new lymphatics, comprises a series of complex cellular events in vitro or in vivo, e.g., proliferation, differentiation, and sprouting. Recent evidence has implied that macrophages act as a direct structural contributor to lymphatic endothelial walls or secret VEGF-C/-D and VEGF-A to initiate lymphangiogenesis in inflamed or tumor tissues. Bone marrow-derived macrophages are versatile cells that express different functional programs in response to exposure to microenvironmental signals, and can be identified by specific expression of a number of proteins, F4/80, CD11b, and CD68. Several causative factors, e.g., NF-κB, IL-1β, TNF-α, SDF-1, M-CSF, especially TonEBP/VEGF-C signaling, may be actively involved in macrophage-induced lymphangiogenesis. Alteration of macrophage phenotype and function has a profound effect on the development and progression of inflammation and malignancy, and macrophage depletion for controlling lymphangiogenesis may provide a novel approach for prevention and treatment of lymphatic-associated diseases.